1997
DOI: 10.1590/s0074-02761997000800015
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines in the modulation of eosinophilia

Abstract: In this review we discuss our recently results showing interleukin 5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
1
7
0
2
Order By: Relevance
“…Both our own findings and literature data seem to indicate that parasitic invasions induce immune and inflammatory response, with the involvement of blood platelets and release of IFN-γ , IL-8, TNF-α and IL-5 [25,38].…”
Section: Studies Of Other Authors Have Shown That In Gsupporting
confidence: 74%
“…Both our own findings and literature data seem to indicate that parasitic invasions induce immune and inflammatory response, with the involvement of blood platelets and release of IFN-γ , IL-8, TNF-α and IL-5 [25,38].…”
Section: Studies Of Other Authors Have Shown That In Gsupporting
confidence: 74%
“…to infect host cells and modulated immune response for surviving within the host. It was reported that the IL-5 cytokine stimulates eosinophil degranulation, production of reactive oxygen species, and exerting a chemotactic effect on these cells [39]. Nickdel et al [40] discussed that T. gondii infection cause's eosinophilia and increased the level of IL-5, with pathological changes in the small intestine, with a simultaneous reduction in IL-12 and IFN-γ.…”
Section: Discussionmentioning
confidence: 99%
“…Another mechanism for initiating the proteolytic cascade is induced by engagement of TNFR, Fas/APO-1/CD95, triggering caspase-3 activation by activated-caspase-8 without involvement of mitochondria [41,42]. Regarding the ligand of TNFR, TNF-α, it has been reported to be released from epithelial cells [43] and activated eosinophils [44]. Moreover, it is known that poly (ADP-ribose) polymerase (PARP) is cleaved by caspase-3, a downstream caspase of caspase-8, -9, and -12, and causes cell apoptosis [45].…”
Section: Introductionmentioning
confidence: 99%